Contemporary Issues and Advancements in Coastal Eolianite Research - David H. Backus (Journal of Marine Science and Engineering)
This review of eolianite research—following a comprehensive overview earlier this century—looks at several areas of overlapping research in coastal eolianite deposition, including the following: tectonic setting; carbonate–sediment type and source areas (carbonate factories); the relationship between relative sea-level change and eolianite deposition; and the evolution of depositional models. Several locations are highlighted in order to emphasize the variety in the eolianite depositional record based on more recent research. In particular, a historical review of eolianite depositional models developed over the last 100-plus years indicates that purely high-stand models of the last century—developed on steep-sided carbonate platforms—do not adequately reflect the complex depositional histories found on other coastal shelves. More recent depositional models emphasize high-stand carbonate production followed by the mobilization of shelf sediments during subsequent relative drops in sea level.